(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The article explores the origin, formation, and genre-stylistic evolution of the novel genre in Kazakh literature of the early 20th century. The primary objects of the study are the pioneers of national prose: «Bakhtsyz Zhamal» by M. Dulatov, «Kalyn Mal» by S. Kobeyev, as well as the novels «Kamar Sulu» and «Kim Zhazykty?» by Sultanmakhmut Toraigyrov. The paper comprehensively analyzes the patronal and educational contributions of early 20th-century periodicals (the «Kazakh» newspaper and «Aikap» magazine) to the emergence of the novel genre, including the historical significance of the novel competition announced by Yesengul kazhy Mamanov. At an artistic level, the study examines issues of women's inequality, social contradictions, the consequences of colonial policy, and the spiritual crisis between generations in S. Toraigyrov's works. Furthermore, the paper theoretically substantiates the harmony of lyricism and prose in the author’s works, the application of folklore traditions and ethnographic elements, and the function of portraiture and epistolary-dialogue forms in revealing character psychology. As a result of the research, it is proven that despite the short length of Kazakh novels in the early 20th century, they attained the level of fully-fledged realistic novels in terms of their thematic density and social significance.